Evolution of Public Debt in Albania during 1990-2017 and its impact on the Economic Growth (European Journal of Marketing and Economics, 2021)
Public debt is one of the most important macroeconomic indicators due to its impact on the economy of each country. Literature suggests that the effect varies in each country depending on the level of economic development and situation. Public debt will have a direct impact on a country's economic growth, but there are contrasting opinions amongst economists regarding the use of public debt, particularly in situations of distress and in developing countries. Albania is a country that would be in need of a decrease of the debt/GDP ratio. This can be done through a stimulation of the economy rather than a decrease of the public debt. The empirical analysis shows that the increase on real public debt can negatively influence the GDP, yet, we do not observe a specific level above which the effects worsened. Instead, we notie that whenever the public debt was increasing, the cost of debt would sometimes decrease because the governments substitutes the debt borrowed from second tier banks with debt borrowed from the IMF.
Keywords: evolution, public, debt, Albania, 1990-2017, impact, economic, growth